2015
DOI: 10.3998/ark.5550190.p008.896
|View full text |Cite
|
Sign up to set email alerts
|

Efficient access to novel 5-aryloyl-1H-pyrano[2,3-d:6,5-d']dipyrimidine-2,4,6,8(3H,5H,7H,9H)-tetraones and their sulfur analogs in water

Abstract: An efficient chemoselective synthesis of novel substituted pyrano [2,3-d]pyrimidines is described. A number of pyrano[2,3-d:6,5-d']dipyrimidine-2,4,6,8(3H,5H,7H,9H)-tetraones and their sulfur analogs were synthesized through a one-pot condensation of arylglyoxal monohydrates with barbituric acid and thiobarbituric acid in the presence of excess ammonium acetate in water at room temperature, affording the desired products in moderate to good yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…They obtained the desired products through an excess ammonium acetate-catalyzed one-pot condensation of aryl glyoxal monohydrate 1 with barbituric acid 19 using the greenest solvent water at room temperature (Scheme 39). 69 Rimaz and co-workers reported the synthesis of pyranofused pyrimidines derivatives 75 by the regioselective pseudothree-component condensation reaction of aryl glyoxal monohydrate 1 and 1-ethyl-2-thioxodihydropyrimidine-4,6(1H,5H)dione 19 under a catalytic system employing DABCO or ZrOCl 2 $8H 2 O in ethanol at 50 °C. The pyrano-fused-pyrimidine scaffold in the synthesized compound was identied as possessing HIV integrase inhibitor activity (Scheme 40).…”
Section: Synthesis Of Pyran Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…They obtained the desired products through an excess ammonium acetate-catalyzed one-pot condensation of aryl glyoxal monohydrate 1 with barbituric acid 19 using the greenest solvent water at room temperature (Scheme 39). 69 Rimaz and co-workers reported the synthesis of pyranofused pyrimidines derivatives 75 by the regioselective pseudothree-component condensation reaction of aryl glyoxal monohydrate 1 and 1-ethyl-2-thioxodihydropyrimidine-4,6(1H,5H)dione 19 under a catalytic system employing DABCO or ZrOCl 2 $8H 2 O in ethanol at 50 °C. The pyrano-fused-pyrimidine scaffold in the synthesized compound was identied as possessing HIV integrase inhibitor activity (Scheme 40).…”
Section: Synthesis Of Pyran Derivativesmentioning
confidence: 99%
“…They obtained the desired products through an excess ammonium acetate-catalyzed one-pot condensation of aryl glyoxal monohydrate 1 with barbituric acid 19 using the greenest solvent water at room temperature (Scheme 39). 69…”
Section: Use Of Aryl Glyoxal In Designing O-heterocycles Using Multic...mentioning
confidence: 99%
“…Rimaz et al 138 reported a highly regio-chemoselective synthesis of pyrano[2,3-d:6,5- d ′]dipyrimidine-2,4,6,8-(3 H ,5 H ,7 H ,9 H )-tetraones 102 and its sulfur analogue by reacting 100 (1 mmol) with 12 (2 mmol) in excess ammonium acetate (5 mmol) and water at RT ( Scheme 72 ). Only in 4-Cl and 4-F analogues of 102 undergo keto–enol tautomerism in DMSO- d 6 solution, but the leading tautomer was keto only.…”
Section: Synthesis Of 5-aryl-substituted Pyrano[23- D ...mentioning
confidence: 99%
“…Rimaz et al 120 reported multicomponent one-pot reactions of aryl glyoxal monohydrates 46 (1 equiv.) with (thio)barbituric acids 47 (2 equiv.)…”
Section: Synthesis Of Tricyclic Systemsmentioning
confidence: 99%
“…The mechanism of this reaction was projected by the formation of N,N-dimethyl-formamidine intermediate from the reaction of 4H-pyran 43 with DMF-DMA, pyrimidine ring cyclization by reaction with hydrazine hydrate, condensation of the amino group of 44 with aryl aldehydes, and imino group with dichloro(phenyl)-phosphine, hydrolysis, tautomerization, and triazaphosphinine ring cyclization through the Pudovik reaction. 119 Rimaz et al 120 reported multicomponent one-pot reactions of aryl glyoxal monohydrates 46 (1 equiv.) with (thio)barbituric acids 47 (2 equiv.)…”
Section: Synthesis Of Tricyclic Systemsmentioning
confidence: 99%